Pengaruh Latihan Celtics Drill Terhadap Peningkatan Daya Tahan (Vo2 Max) Pada Pemain Bola Basket Putra MAN 2 Mataram - Wira Kusuma, Dadang Warta Candra; Syobri, Nazalus; Marzuki, Ismail (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The purpose of this study was to determine whether or not there was an effect of Celtics drill training on increasing Endurance (VO2 Max) in MAN 2 Mataram men's basketball players. In this study using quantitative methods, with experimental research methods. The subjects in this study were MAN 2 Mataram basketball players who joined the MAN 2 Mataram basketball extracurricular. The research results obtained were on endurance (VO2 Max) pre-test maximum 45.5 minimum 32.6 and post-test maximum 46.5 and minimum 34.7. From the calculation of the T test, the results were 3.317, while the T-table value was 1.769. so it can be concluded that there is an effect of Celtics drill training on increasing endurance (VO2 Max) in men's basketball players MAN 2 Mataram.